2017
DOI: 10.1038/s41598-017-11565-7
|View full text |Cite|
|
Sign up to set email alerts
|

QTL mapping and molecular characterization of the classical D locus controlling seed and flower color in Linum usitatissimum (flax)

Abstract: The flowers of flax (linseed) are blue-hued, ephemeral and self-pollinating, and the seeds are typically brown. A century-old interest in natural yellow seed variants and a historical model point to recessive alleles in B1, D and G loci being responsible, but the functional aspects had remained unknown. Here, we characterized the “D” locus by quantitative trait loci (QTL) mapping and identified a FLAVONOID 3′5′ HYDROXYLASE (F3′5′H) gene therein. It does not belong to the F3′5′H clade, but resembles biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 60 publications
(87 reference statements)
4
25
0
1
Order By: Relevance
“…QTL for seed coat color to indirectly increase oil content and minimize HC have been identified in B. napus and soybean [ 37 , 59 , 60 ]. In flax, a pleiotropic QTL controlling yellow seed and white flower color was recently dissected at the molecular level, but its effect on HC has not been addressed [ 23 ]. Here, we identified four QTL whose effects reduced HC by 2.6%, on average.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QTL for seed coat color to indirectly increase oil content and minimize HC have been identified in B. napus and soybean [ 37 , 59 , 60 ]. In flax, a pleiotropic QTL controlling yellow seed and white flower color was recently dissected at the molecular level, but its effect on HC has not been addressed [ 23 ]. Here, we identified four QTL whose effects reduced HC by 2.6%, on average.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation for MC and HC in flaxseed has been assessed [ 4 , 7 , 16 , 17 , 18 ] but no quantitative trait loci (QTL) have been reported so far. QTL for Fusarium wilt resistance [ 19 ], powdery mildew [ 20 ], iodine value, palmitic, linoleic, and linolenic acids [ 21 , 22 ], and seed and flower color [ 23 ], were reported. QTL for seed protein, cell wall, straw weight, yield-related traits, and phenological traits, have also been reported using bi-parental mapping and association mapping [ 22 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cloutier et al construct a consensus linkage map by combined three individual linkage maps incorporating 770 markers based on 371 shared markers including 114 that were shared by all three populations and 257 shared between any two populations [ 14 ]. Most of the QTL mapping analysis focused on fatty acid related traits, such as fatty acid composition, yield [ 15 , 16 ], seed and flower color [ 17 ]. For example, Sudarshan et al,(2017) identified a seed and flower color QTL “D” by QTL mapping analysis and identified a candidate gene [ 17 ].Today, SNP markers are the most efficient and abundant markers for mapping [ 18 ] and other applications, such as GWASs [ 19 , 20 ], diversity analyses [ 21 ] and bulked segregate analysis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identified 183 seed oil QTLs in soybean, which was annotated as part of Soybase database (Grant et al 2009), providing key information related to seed development and associated molecular mechanism to set up soybean as a model legume crop (Gupta et al 2017). In a very interesting study Sudarshan et al (2017) characterized "D" locus Linum usitatissimum (flax) by QTL mapping and identified an underlying FLAVONOID 3′5′ HYDROXYLASE (F3′5′H) gene which determine the seed and flower color. A single nucleotide deletion in this gene truncates the deduced product thus leading to yellow seed and white flower phenotypes in flax (Sudarshan et al 2017).…”
Section: Quantitative Trait Loci (Qtls) and Genome Wide Association Smentioning
confidence: 99%